Integration of Maqasid al-Shari'ah Principles in Sustainable Consumption: An Innovative Solution Toward Achieving the SDGs - Mokhammad Ainurrofiq (FADZAT: Jurnal Ekonomi Syariah, 2025)
This study explores how the Maq??id al-Shar?'ah principle can be a relevant ethical foundation to promote sustainable consumption in line with the Sustainable Development Goals (SDGs). Utilizing rich secondary data from various global sources, this study shows that the halal energy, transportation and supply chain sectors have a major contribution to make in reducing environmental impacts. Key results reveal that green sukuk can reduce carbon emissions by 40% in the energy sector and 20% in the transportation sector, while halal literacy programs have successfully increased consumer preference for sustainable products from 60% to 85%. The findings also highlight challenges, such as lack of public awareness and mismatches between global and local standards, which can be addressed through green technology innovation and the development of halal products that support sustainability. By integrating Islamic values and global needs, this research offers strategic guidance to create a balance between economic development and environmental preservation.